Developing Listening Skill Materials in the 8th Grade English Module - Silvia, Silvia; Susilawati, Susilawati; Siniawati, Siniawati (Ma'soem University, 2024)
In the context of increasing globalization and communication, listening skills become an important skill. Therefore, developing listening skills is very important so that someone can communicate effectively and understand various accents, intonations, and language variations used in conversation. This study aims to develop a learning module in the field of listening skills at the 8th grade junior high school/Islamic junior high school level. The module is designed to help students improving their ability to understand foreign languages and train students in using audio. This study used the R&D method from Sugiyono (2013) and used the Borg and Gall model and uses 6 steps in making this learning module, namely, needs analysis, designing learning module designs, product design/product preparation, product evaluation, product trials, and dissemination. By going through these stages, the results of the study show that the open listening skills module book using audio significantly improves listening skills compared to traditional methods. This learning module can be used by students and teachers easily and can be accessed at home or at school using gadgets or laptops.